Bax/Bcl-2 Ratio as the Golden Marker of Apoptosis: Molecular Mechanisms and Regulatory Pathways - Putri, Ghea Farmaning Thias; Nurfatihah Z, Zahara (International Journal of Cell and Biomedical Science, 2025)
Apoptosis is an essential biological mechanism responsible for maintaining tissue homeostasis by removing unnecessary or damaged cells. Among the key molecular regulators, the interplay between the pro-apoptotic protein Bax and the anti-apoptotic protein Bcl-2 determines cellular fate. The Bax/Bcl-2 ratio has been recognized as the “golden marker” of apoptosis, representing the fine equilibrium between survival and death signaling pathways within cells. This review aims to provide an updated overview of recent advances in understanding the molecular mechanisms and regulatory networks that control the Bax/Bcl-2 ratio and its significance as a diagnostic and therapeutic biomarker. Relevant studies were systematically identified from PubMed, Scopus, ScienceDirect, and Google Scholar, focusing on publications from 2020 to 2025. Current evidence suggests that the Bax/Bcl-2 ratio is influenced by transcriptional regulation involving p53, NF-κB, and Akt/PI3K pathways, as well as by post-translational modifications such as phosphorylation and ubiquitination that govern mitochondrial membrane permeabilization. Clinically, alterations in this ratio correlate with disease progression, therapeutic response, and prognosis in cancer, neurodegenerative, and renal disorders. Targeting this ratio through modulation of upstream regulators or BH3 mimetics offers promising therapeutic potential. In conclusion, a deeper understanding of the Bax/Bcl-2 ratio provides crucial perspectives for advancing diagnostic innovation and developing targeted therapies for apoptosis-related diseases.